Power Knowledge: The Importance Of “Capital” Of Employee - Tasrim Tasrim; Risman Risman; Ansri Jayanti (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
Human resources become an important "support" in the survival of the company's "life". The company is able to move due to the existence of a workforce that is "owned" by the company. This study describes the important role of employees as one of the "capital" of the company. Postmodernists are used to see the social reality of employees. This research is a qualitative research with the interview method as the main data collection. The informant selected was the head of the company's Human Resources Development (HRD). The location of the research was a sugar company in Makassar City, Indonesia. The epistemological approach chosen is the knowledge-power of Michel Foucault with his three “surgical” tools, namely sharing, generating, and using knowledge, unlimited interpretation is used to parse the research results. The results show that employee capital is a cycle of human capital. This capital has two important things attached to it, namely producing and generating value. Then these two things make it the company's highest asset. Employees and their knowledge as inherent so that when employees "go" leave the company, the knowledge goes with it. Companies must be able to transfer knowledge between employees and the company, although there are certain skills that may be "difficult" to "transfer".